Development of 20 kVA Convertor Module - XIONG Min; JIAN Fang; ZHANG Xiaoyong (Kongzhi Yu Xinxi Jishu)
It introduces main circuit, general structure and technical characteristics of the self-developed 20 kVA convertor module. The convertor module has been used in 200 km/h EMUs with good running performance.